2008
DOI: 10.1016/j.cyto.2008.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed cytokine detection of interstitial fluid collected from polymeric hollow tube implants—A feasibility study

Abstract: Cytokines are important cellular signaling proteins involved in inflammation, wound healing and are thought to direct the foreign body response to implanted materials. In this work, polyurethane tubes (25 mm length, 1.02 mm i.d., and 1.65 mm o.d.) were implanted into subcutaneous tissue of male Sprague-Dawley rats. The tubes served as the biomaterial and a means to collect the interstitial fluid that would be exchanged within the tube lumen and the surrounding tissue. After three and seven days, the tubes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Two studies have investigated the physiological levels of cytokines present within an implanted hollow biomaterial tube [44,45]. Unfortunately, the outcomes obtained in those in vivo studies were constrained by the protocol employed: the subcutaneous implantation of the tube resulted (not surprisingly) in encapsulation.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have investigated the physiological levels of cytokines present within an implanted hollow biomaterial tube [44,45]. Unfortunately, the outcomes obtained in those in vivo studies were constrained by the protocol employed: the subcutaneous implantation of the tube resulted (not surprisingly) in encapsulation.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the response of the body after implantation of biomaterials, the in vivo determination of different cytokines has recently been used in several studies [8][9][10][11]. Furthermore, a recent study which found that variations in the genes of cytokines including IL-2 and IL-6 influence the severity of osteolysis in patients with total hip arthroplasty demonstrates the potential relevance of cytokines for implant-associated complications [12].…”
Section: Introductionmentioning
confidence: 98%
“…In our experience with sampling cytokines, it is rare to achieve a steady-state concentration. Cytokine concentrations can be quite variable, and for implanted objects, the concentrations can be in the low 10- to 100-pg/mL range [39-42], which, combined with microdialysis sampling extraction efficiencies, will lead to non-quantifiable concentrations. To obtain more consistent cytokine concentrations, we chose to use LPS to induce cytokine production, as previously demonstrated in mice [43].…”
Section: Resultsmentioning
confidence: 99%